Penerapan Teknik Shadowing dalam Kegiatan Menyimak Bahasa Jepang pada Siswa Kelas X SMA - Lusi Asmaraningtyas; Ina Ika Pratita; Miftachul Amri (LP. Ma'arif Janggan Magetan, 2024)
Listening is the most basic skill in language learning. A voice that cannot be heard, cannot be pronounced properly. If you don't understand what the other person is saying, then you can't participate in communication. The purpose of this study was to find out the results of the application of the Shadowing learning model in listening to Japanese learning activities for class X students at SMAN 5 Malang, specifically focusing on Chouon (long vowel) with the theme